Panati's extraordinary origins of everyday things - Panati, Charles, 1943- (New York Perennial Library, 1989)
The origins of words and phrases, superstitions, manners and customs, holidays, kitchen utencils, household appliances, household supplies, fairy tales, nursery rhymes, cosmetics, medicines, clothing, national emblems, patriotic societies, periodicals, toys, games, and foods
Includes index
Keywords: Encyclopedias and dictionaries